Analisis Syair Burdah Imam Bushiri Bab 1 dalam tinjauan Stilistika Linguistik sebagai penunjang dalam pemaknaan dan penyusunan kalimat - Mohammad Harris Yanuardi (Institut Agama Islam Pemalang (INSIP) Jawa Tengah, 2024)
This research aims to analyze the elements of stylistic language found in Chapter 1 of the Burdah by Imam Bushiri by examining various levels of linguistics, including phonology, morphology, syntax, semantics, and imagery. The background of this research stems from the need to understand how stylistic language influences meaning in classical Arabic poetry. The main issue in this research is to discuss the relationship between linguistic aspects and their impact on text interpretation. The methodology used is descriptive qualitative, with the type of research being library research. The data analysis technique in this study involves content analysis of selected excerpts from Chapter 1 of the Burdah by Imam Bushiri. The researcher acts as the primary instrument in data collection. The data sources in this study consist of the text of Chapter 1 of the Burdah as primary data and previous research as secondary data. The results of this study explain the deviations of language in literature and identify the stylistic devices used, which have implications for enhancing understanding of the text's meaning by providing a framework for analyzing classical Arabic poetry. This research contributes to the field of stylistics to enrich appreciation for the literary art of Imam Bushiri.